Answer:
The expression that equivalent to
is 3
⇒ C
Explanation:
Let us revise some rule of exponents
=
![a^(m-n)](https://img.qammunity.org/2022/formulas/mathematics/high-school/9io2omhuqm7ufajmxgb5egrkixlc20j317.png)
=
![a^(mn)](https://img.qammunity.org/2022/formulas/mathematics/high-school/cmsd2gfv2pql9zrvq0ifgu4i63g47fufzy.png)
Let us solve the question
∵ The expression is
![(12x^(4))/(4x^(16))](https://img.qammunity.org/2022/formulas/mathematics/high-school/ywsi9a6hsz1qfyn9omx1w29j0yfbr26j6d.png)
→ Simplify the fraction 12/4 first
∵ 12/4 = 3
∴
= 3 (
)
→ By using the second rule above to simplify the variable
∵
=
![x^(4-16)](https://img.qammunity.org/2022/formulas/mathematics/high-school/anw9m2sk7n8mioevwwlzkmlkxmpyt1z88y.png)
∴
= 3
![x^(4-16)](https://img.qammunity.org/2022/formulas/mathematics/high-school/anw9m2sk7n8mioevwwlzkmlkxmpyt1z88y.png)
∴ The expression that equivalent to
is 3
![x^(4-16)](https://img.qammunity.org/2022/formulas/mathematics/high-school/anw9m2sk7n8mioevwwlzkmlkxmpyt1z88y.png)